Seagrass Connectivity on the West Coast of Africa Supports the Hypothesis of Grazer-Mediated Seed Dispersal - Tavares, Ana I.; Assis, Jorge; Patrício, A. R.; Ferreira, Rogério; Cheikh, Mohamed Ahmed Sidi; Bandeira, Salomão; Regalla, Aissa; Santos, Iderlindo; Potouroglou, Maria; Nicolau, Suzana; Teodósio, Maria Alexandra; Almada, Carmen; et al. (Frontiers in Marine Science, 2022)
Population connectivity influences the distribution of genetic diversity and divergence along a species range, as the likelihood of extinction or differentiation increases in isolated populations. However, there is still poor understanding of the processes mediating inter-population dispersal in marine species that are sessile and lack planktonic life stages. One such case is the seagrass species Halodule wrightii, which produces basal seeds, although detached plants can drift. Along the tropical western coast of Africa, this species occurs in distant discontinuous habitats, raising the question of how interpopulation dispersal is mediated. The species is a key source of ecosystem functions including feeding large migratory grazers. This study aims to infer whether genetic differentiation of the seagrass H. wrightii along the western coast of Africa supports a hypothesis of predominant transportation of rafting seagrass by ocean currents, versus the hypothesis of biotic vectors of dispersal. Additional hypotheses were addressed concerning range-wide clonality and genetic diversity, assessed with microsatellite markers on populations of the west coast of Africa from Mauritania to Angola. Population genetic diversity and structure were compared with predictions from biophysical models of dispersal by oceanographic currents. The genetic data revealed low divergence among most populations, in strong contrast with predictions of very low probability of connectivity mediated by currents along the western African coastline. Moderate to high genotypic diversity showed important seed recruitment, but genetic and genotypic diversities were lower at range edges. Populations north and south of the equator were differentiated, and remarkably, so were neighboring equatorial populations despite their proximity. These results reveal independent sources of colonization of meadows in these islands, which are major habitat for migratory grazing green turtles, also supporting the hypothesis of biotically mediated seed transport. The importance of seagrass for conservation of endangered macrofauna has been widely reported; here we report evidence supporting the reciprocal role, that macrofauna protection can also plays a role in long-term survival and reproductive success of seagrass.